Chromosomal rearrangement segregating with adrenoleukodystrophy: a molecular analysis. - Sack, G H (1993)
The relationship between X chromosome-linked adrenoleukodystrophy and the red/green color pigment gene cluster on Xq28 was investigated in a large kindred. The DNA in a hemizygous male showed altered restriction fragment sizes compatible with at least a deletion extending from the 5' end of the color pigment genes. Segregation analysis using a DNA probe within the color pigment gene cluster showed significant linkage with adrenoleukodystrophy (logarithm of odds score of 3.19 at theta = 0.0). These data demonstrate linkage, rather than association, between a unique molecular rearrangement in the color pigment gene cluster and adrenoleukodystrophy. The DNA changes in this region are thus likely to be helpful for determining the location and identity of the responsible gene.